(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The main objective of this research was to establish the effect that teaching and learning methods have on the attitude and performance of the learners of chemistry in grade 11 in selected schools of Chipata district. The research method employed was survey in which questionnaires were used to obtain information on the various methods that teachers use in the teaching and learning and how it impacts on the attitudes and performance of learners in chemistry. A positive correlation (r=0.057) (p<0.05) exist between the teaching and learning and the attitudes and performance of grade 11 learners of chemistry. Therefore, teaching and learning of chemistry has an impact on the attitude and performance for grade 11 learners in Chipata district. > The main objective of this research was to establish the effect that teaching and learning methods have on the attitude and performance of the learners of chemistry in grade 11 in selected schools of Chipata district. The research method employed was survey in which questionnaires were used to obtain information on the various methods that teachers use in the teaching and learning and how it impacts on the attitudes and performance of learners in chemistry. A positive correlation (r=0.057) (p<0.05) exist between the teaching and learning and the attitudes and performance of grade 11 learners of chemistry. Therefore, teaching and learning of chemistry has an impact on the attitude and performance for grade 11 learners in Chipata district.